Modelo relacional de análise de percepções de injustiça, estresse ocupacional e retaliação em organizações: um estudo com jovens trabalhadores - Jesuina Maria Pereira Ferreira (2018)
Considered contemporary constructs, the literature of occupational stress, justice and retaliation take into account the analysis of the organizational context in which the individual is inserted. In the area of people management, these constructs are considered to be counterproductive behaviors, most of the times by organizations and little explored the possible relationships between them. This paper presents the state of the art of occupational stress, justice / injustice and retaliation in organizations, their main dimensions and latest research. The objective of this research was to propose, adjust and validate the model that integrates occupational stress constructs, perception of injustice and retaliation in organizations according to the perception of young workers assisted by the Association of Professional Social Teaching (ESPRO). The methodological approach was mixed, composed of two steps. The first step was quantitative and exploratory, seeking to validate the selected constructs and dimensions of the literature on occupational stress, justice and retaliation in organizations and to understand their relationships through the analysis of the hypotheses proposed. Subsequently, the second step of qualitative approach sought to understand how these constructs are perceived and explained through behavior at work. Data collection was done through a questionnaire (Step 1) and semi-structured interview (Step 2). The quantitative data analysis involved the factorial analysis of the data, the structural equations modeling and the descriptive analysis of the data and the qualitative data analysis was performed by the content analysis. Among the main results, we highlight the proposition and test of an unrelated relational model composed of 8 constructs, 15 dimensions and 49 variables, involving theories of occupational stress, justice and retaliation in organizations. In addition, it is pointed out that the relevant findings of this thesis have demonstrated the existence of important relations of influence both internal and external between occupational stress constructs, justice and organizational retaliation. External relations between the constructs of occupational stress and organizational justice, and between the constructs of organizational retaliation and justice were validated. Between occupational stress and organizational justice, validated external relations were among the constructs sources of dissatisfaction and perceptions of justice, and perceptions of justice and coping strategies of perceived stress. With respect to organizational retaliation and justice, the proven external relationship was between constructs perceptions of justice and coping strategies of perceived injustice (retaliatory actions). The only invalidated external relationship was between the constructs of occupational stress and retaliation in organizations that verified the relationship of influence between the same construct of retaliation (strategies to cope with perceived injustice) and occupational stress constructs (sources of pressure, sources of dissatisfaction and coping strategies of perceived stress). Therefore, it was concluded that the relationship between occupational stress and retaliation is not realized through the investigated constructs, and should be explored by other researches, which also constitutes an important data for the studies on these themes. Finally, the results of this thesis contribute to public and private organizations to improve their policies and rules so that they generate professional and personal transformations for the young workers who are involved in them.